Analysis of Innovation in Public Transport Services Management Based on Plastic Waste in Support of The SDGS: A Study of Trans Semanggi Suroboyo - Alifatu Azwa Shoima; Nayshira Rieva Candra; Meirnawati; Trenda Aktiva Oktariyanda (PT. Maju Malaqbi Makkarana, 2026)
This study examines the innovation of public transport service management through a platic waste-based payment in the Trans Semanggi Suroboyo (TSS) service in Surabaya City. The study aims to analyse the effectiveness of this innovation in supporting sustainable urban transport development, particularly in relation to Sustainable Development Goals (SDGs) 11. A qualitative descriptive approach was employed, using secondary data collected from scientific literature, official reports, and regulatory documents. The analysis was conducted using George C. Edward III’s policy implementation framework, focusing on communication, resources, disposition, and bureaucratic structure. The finding indicate that this innovation contributes positively to environmental management and promotes public participation in waste reduction while improving transport accessibility. However, its implementation faces several challenges, including limited fleet availability, inadequate infrastructure, fragmented communication, and key to integrity between payment system. These constraints affect service efficiency and user satisfaction. Therefore, strengthening policy coordination, improving infrastructure, enhancing human resource capacity, and optimizing public communication are necessary to support the sustainability and effectiveness of this innovation. This study highlights that integrated and adaptive public transport innovations are essential in achieving inclusive, efficient, and sustainable urban mobility in line with SDGs 11.